Characteristics of Tropical Drained Peatlands and CO2 Emission under Several Land Use Types - Wigena, I Gusti Putu; Husnain, .; Susanti, Erni; Agus, Fahmuddin (JOURNAL OF TROPICAL SOILS, 2015)
Converting of tropical rain forest into plantation and agriculture land uses has been claimed as a main factor that affects to global warming and climate change. In order to provide a comprehensive information of the issue, a field observation on peat properties in relation to CO2 emission under several land use types had been done at Lubuk Ogong Village, Pelalawan District, Riau Province from May 2011-April 2012. Five land use types, namely A. mangium, bare land, oil palm, rubber, and secondary forest have been selected in the study site. Observations were made for chemical and physical properties, above and below ground C-stock and CO2 emissions. The results showed a higher variation of peat depth and a below ground C-stock was almost linearly with a peat depth. Below ground C-stock for each land use was around 2848.55 Mg ha-1, 2657.08 Mg ha-1 5949.85 Mg ha-1, 3374.69 Mg ha-1, 4104.87 Mg ha-1 for secondary forest, rubber, oil palm, bare land, and A. mangium, respectively. The highest above ground C-stock observed on a secondary forest was 131.5 Mg ha-1, followed by the four years A. mangium 48.4 Mg ha-1, the 1-2 years A. mangium 36.6 Mg ha-1, and the 4 years A. mangium 34.4 Mg ha-1. While, CO2 emissions in the study sites were 66.58±21.77 Mg ha-1yr-1, 66.17±25.54 Mg ha-1yr-1, 64.50±31.49 Mg ha-1yr-1, 59.55±18.30 Mg ha-1yr-1, 53.65±16.91 Mg ha-1yr-1 for bareland, oil palm, secondary forest, A. mangium, and rubber, respectively. [How to Cite: IG Putu Wigena, Husnain, E Susanti, and F Agus. 2015. Characteristics of Tropical Drained Peatlands and CO2 Emission under Several Land Use Types. J Trop Soils 19: 47-57. Doi: 10.5400/jts.2015.20.1.47][Permalink/DOI: www.dx.doi.org/10.5400/jts.2015.20.1.47]